Death and hospital contact in a cohort from Thyborøn-Harboøre an environmentally contaminated site in Denmark - Elsebeth Lynge; Hans Holmsgaard; Jørgen Bjerggaard Jensen; Søren Lophaven (Scientific Reports)
Abstract We studied mortality and hospital contact in people from Thyborøn-Harboøre, an environmentally contaminated fishing community on the Danish West Coast. The population and a comparison group from other fishing communities on the Danish West Coast were identified from historical data in the Central Population Register. All persons were followed up for death and hospital contacts to March 2023. Event rates were compared with Poisson regression; adjusted rate ratios (aRR); and 95% confidence interval (CI). The old cohort included inhabitants in Thyborøn-Harboøre in 1968–1970 before pollution was controlled; 4914 persons/2485 deaths. All-cause mortality, aRR 1.06 (95% CI 1.01–1.11), and cancer mortality, aRR 1.17 (95% CI 1.05–1.30), were elevated; especially for kidney cancer aRR 1.82 (95% CI 1.07–3.12). Hospital contacts were elevated for psychiatric disorders; with an aRR of 4.07 (95% CI 1.41–11.72) for anxiety in men. As there is still considerable concern in the area about possible health consequences from stored chemicals, we included also a new cohort of newborn and immigrants to the area in 1990–2006; 2933 persons/302 deaths. All-cause mortality, aRR 1.26 (1.11–1.43) (men 1.15 and women 1.44), and cancer mortality, aRR 1.47 (95% CI 1.14–1.89) were elevated. Hospital contacts were elevated for ischemic heart disease/heart attack and indicated for autism/obsessive compulsory disorder in boys. In conclusion, mortality data confirmed incidence data of excess kidney cancer in the old cohort. The new cohort had a generally elevated mortality, possibly indicating selective immigration from other parts of Denmark. However, the new cohort is still relatively young, and the mortality pattern needs to be monitored.